2001
DOI: 10.1097/00061198-200106000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Scan Radius Correction for Ocular Magnification and Relationship Between Scan Radius With Retinal Nerve Fiber Layer Thickness Measured by Optical Coherence Tomography

Abstract: To increase the accuracy of RNFL thickness measurements, it will be appropriate for the examiner to manually correct the actual scan parameters to the desired or preset ones after their automatic modification performed by the OCT instrument. Keeping the actual scan radius constant for repeated exams is also recommended because RNFL thickness measurements were found to depend on scan size. Alternatively, RNFL(estimated integrals) could be used because they were found to be independent of the scan size.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 16 publications
2
46
1
Order By: Relevance
“…Only minimal differences within 5 µm in thickness were detected in most of the sections, including central macular thickness (table 3). Bayraktar et al [5] reported that if an area of 1.73 mm in diameter is used to analyze RNFL thickness, the area of interest will expand by 0.06 mm as the axial length increases by 1 mm. As a result, areas that are further away from the borders of the optic disc will be analyzed, resulting in a lower value of RNFL thickness.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Only minimal differences within 5 µm in thickness were detected in most of the sections, including central macular thickness (table 3). Bayraktar et al [5] reported that if an area of 1.73 mm in diameter is used to analyze RNFL thickness, the area of interest will expand by 0.06 mm as the axial length increases by 1 mm. As a result, areas that are further away from the borders of the optic disc will be analyzed, resulting in a lower value of RNFL thickness.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the measurements obtained may be affected by axial length of the eyes and refractive power [4,5]. However, there have been few clinical investigations regarding the extent to which this influences the results.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that AL-induced magnification can affect the OCT scan radius, 19 the effect of magnification on OCT macular measurements should be considered in myopic eyes. Because the methodology for correction of the magnification effect on macular thickness/volume measured using OCT remains unclear in previous studies, [6][7][8][9][10][11][13][14][15] the effect of magnification was not corrected as in the present study.…”
Section: Macular Thickness In Myopic Eyes By Spectral-domain Optical mentioning
confidence: 99%
“…10 These methods have been compared by Garway-Heath et al, 9 who concluded that the simplest approach of using only axial length to correct for magnification error was accurate and produced very similar results to the more detailed calculations that incorporated keratometry, refractive error, and lens thickness. 15 Given most eye clinics have access to devices that measure axial length and that incorporating axial length has been shown to increase the accuracy of optic nerve head size and retinal layer thickness evaluated by OCT, [16][17][18][19][20][21][22][23] we hypothesize that OCTA image magnification correction using axial length measurement is feasible and necessary for accurate determination of OCTAderived variables.…”
mentioning
confidence: 99%